(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Introduction Banking is the activity of receiving client deposits of money that are due ondemand for the purpose of lending or investing at other times and may be withdrawn by use of a papercheck, money order, or similar order.Aim of the study the main aim of the study Is to Customers And Their Levels Of Satisfaction WithRegard To The Services Provided By ICICI Bank And SBI BankMaterial and method The research plan is the blueprint for doing the study and interpreting the findings.Conclusion Service providers in India’s banking industry place a premium on happy customers. Whenclients’ needs and wants are understood, Indian financial institutions would be better prepared tocompete.